Intersetorialidade em pol??ticas p??blicas de enfrentamento ?? viol??ncia contra a crian??a e o adolescente - Stacheira, Claudio Roberto (2014)
This study addresses the formalization of knowledge by means of an ontology as a way to promote intersectoral collaboration between sectional public policies involved in ensuring the rights of children and adolescents in Brazil. We use a qualitative, phenomenological approach. We identify the main actors, macro processes and concepts based on the Brazilian Statute of the Child and Adolescent (ECA) and the current practices of the Brazilian Federal Public Administration (APF) concerning the defense of children and adolescents, as well as their relationships. We propose a domain ontology about the process of combating the violence against children and adolescents, analyzing its applicability in the context of a prospective e-government service related to the existing System of Guarantee of Child and Adolescents Rights (SGD), particularly in the field of Linked Open Government Data (LOGD). Our conclusion is that ontologies are strategic to the process of strengthening the capacity building of the state and society in order to promote the rights of children and adolescents, and that children and adolescents rights is a complex area, little explored by the Knowledge Engineering sciences, but it is a fertile ground for research that contributes to the improvement of public management in the child and adolescent area considering the constitutional condition of absolute priority to these citizens affirmed by the Brazilian State.